The butterfly effect hits complicité: a chaotic reading of Mnemonic and A Disappearing Number - Khalid Ahmad Yas,; Arbaayah Ali Termizi,; Rosli Talif,; Hardev Kaur, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The middle ground chaos theory secures among other gigantic scientific theories to describe the world has brought it to the fore lately. It neither declines the Newtonian clockwork model completely nor promotes the quantum indeterministic model entirely. It preaches that the world is both ordered and disordered, and man is both bound and free. Unlike relativity and quantum physics, it is neither busy with massive objects nor preoccupied with tiny ones, the atoms. It simply works in between, our world. Thus, it spreads and is widely utilised in a variety of disciplines, including literary and cultural domains. Conversely, Theatre de Complicité promotes nonlinearity and fragmentation for structure, and physicality and visual imagery for performance. It does not prefer pre-written texts rather favours devising its own through a lengthy process of improvising and rehearsing. It believes that the world is no longer a world of a single story. It cannot be encompassed within one philosophy or viewpoint. Mnemonic and A Disappearing Number suggest human body within the context of origin as a collective identity, and math within the context of infinity as a path for eternity. Hence, chaos theory is deemed to be the appropriate choice for analysis as it can provide an avenue of escape from the soul-crushing mechanical view of the world dominated most critical approaches for decades and can also furnish an alternative language and scope for literary interpretation.